A systematic review of normal-tissue complication models relevant to standard fractionation radiation therapy of the head and neck region published after the QUANTEC reports - Brodin, N. Patrik (Int J Radiat Oncol Biol Phys, 2017)
There has recently been an increasing interest in model-based evaluation and comparison of different treatment options in radiation oncology studies. This is partly driven by the considerable technical advancements in radiation therapy of the last decade, leaving radiation oncologists with a multitude of options to consider. In lieu of randomized trials comparing all of these different treatment options for varying indications, which is unfeasible, treatment evaluations based on normal-tissue complication probability (NTCP) models offer a practical alternative. The Quantitative Analyses of Normal Tissue Effects in the Clinic (QUANTEC) effort culminating in a number of reports published in 2010 provided a basis for many of the since implemented dose-response models and dose-volume constraints, and was a key component for model-based treatment evaluations. Given that seven years have past since the QUANTEC publications and that patient-reported outcomes has emerged as an important consideration in recent years, an updated summary of the published radiation dose-response literature, that includes a focus on patient-reported quality of life outcomes, is warranted. Here, we provide a systematic review of quantitative dose-response models published after January 1(st) 2010 for endpoints relevant to radiation therapy for head and neck cancer, as these patients are typically at risk for a variety of treatment-induced normal tissue complications.